2018
DOI: 10.1080/00036846.2018.1543939
|View full text |Cite
|
Sign up to set email alerts
|

Labour market consequences of a high school diploma

Abstract: This article compares the labour market outcomes of high school dropouts to high school graduates who did not enroll into higher education, but immediately entered the labour market. Using parental educational background as an instrument on a rich administrative dataset in the Flemish Region of Belgium, we find no returns to a high school diploma on average. However, these results hide considerable heterogeneity by gender and educational track. While females and individuals in vocational education may benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Conversely, findings suggesting that soft skills are of similar predictive validity regardless of education level may warrant reconsideration of our conceptions of high school occupations and employees, as well as the job advertisement practices of high school job employers. This research could be supplemented by studies conducted outside of the United States to better understand employer expectations of high school–educated individuals internationally (e.g., Krahn et al, 2002; Mazrekaj et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, findings suggesting that soft skills are of similar predictive validity regardless of education level may warrant reconsideration of our conceptions of high school occupations and employees, as well as the job advertisement practices of high school job employers. This research could be supplemented by studies conducted outside of the United States to better understand employer expectations of high school–educated individuals internationally (e.g., Krahn et al, 2002; Mazrekaj et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, most students actually drop out from vocational education (European Commission, 2013). Dickson & Harmon, 2011;Balestra (the region studied in this article), Mazrekaj et al (2019) found that the labour market outcomes of students with and without a diploma differ depending on the education track a student followed in secondary education (general or vocational education). This is because students in vocational education are trained for a specific profession and to perform specific tasks.…”
Section: Introductionmentioning
confidence: 94%
“…An interesting strand of literature compared the dropout risk and subsequent labour market outcomes of students in general and in vocational education (e.g. Dickson & Harmon, 2011;Balestra (the region studied in this article), Mazrekaj et al (2019) found that the labour market outcomes of students with and without a diploma differ depending on the education track a student followed in secondary education (general or vocational education). Thus, as vocational education students often have different observed and unobserved characteristics than students in other educational tracks (Chankseliani et al, 2016), and as dropout is more multi-dimensional in vocational education, it is unclear whether the results obtained in previous studies for general and pre-university education also hold for vocational education.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the discussion on how to best prepare youth for the labour market centres on whether education should be either vocationally or generally oriented (Ryan, 2001;Eichhorst et al, 2015). Research indicates that vocational education, in comparison to general education, is linked to higher earnings, a shorter job search, and better matches between skills and job requirements at the start of the career (Müller and Gangl, 2003;Mazrekaj, De Witte and Vansteenkiste, 2019). These relative advantages, however, do not seem to persist over time (McIntosh, 2006;Brunello and Rocco, 2017;Rözer and Bol, 2019;Neyt, Verhaest and Baert, 2020) and may, at later points in the career, even turn into disadvantages (Forster, Bol and Van de Werfhorst, 2016;Hampf and Woessmann, 2017;Hanushek et al, 2017;Forster and Bol, 2018;Verhaest et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%